Oral Release Kinetics, Biodistribution, and Excretion of Dopants from Barium-Containing Bioactive Glass in Rats - Majumdar, Shreyasi; Tiwari, Anshul; Mallick, Debasmit; Patel, Devendra K.; Trigun, Surendra Kumar; Krishnamurthy, Sairam (American Chemical Society, 2024)
Background: Inorganic biomaterials are biologically active and are used as implants and drug delivery system. They have therapeutically active elements present in their framework that are released in the physiological milieu. Release of these dopants above the supraphysiological limit may produce adverse effects and physicochemical interactions with the loaded drugs. Therefore, this necessitates evaluating the in vivo release kinetics, biodistribution, and excretion profiles of dopants from barium-doped bioglass (BaBG) that has potential anti-inflammatory, antiulcer, and regenerative properties. Methods: In vitro leaching of Ca, Si, and Ba from BaBG was analyzed in simulated body fluid. Release kinetics post single-dose oral administration (1, 5, and 10 mg/kg) was performed in rats. Blood was collected at different time points, and pharmacokinetic parameters of released elements were calculated. The routes of excretion and biodistribution in major organs were evaluated using ICP-MS. Results: Elements were released after the oral administration of BaBG into the plasma. They showed dose-dependent release kinetics and mean residence time. Cmax was observed at 24 h for all elements, followed by a downhill fall. There was also a dose-dependent increase in the volume of distribution, and the clearance of dopants was mostly through feces. Ba and Si were biodistributed significantly in the liver, spleen, and kidneys. However, by the end of day 7, there was a leveling-off effect observed for all elements. Conclusion: All of the dopants exhibited a dose-dependent increase in release kinetics and biodistribution in vital organs. This study will help in dose optimization and understanding of various physicochemical and pharmacokinetic interactions when BaBG is used for future pharmacological studies.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.